KANDUNGAN MINYAK MALAPARI (Pongamia pinnata (L.) Pierre) DARI PULAU JAWA SEBAGAI SUMBER BAHAN BAKU BIODIESEL - Aam Aminah; Supriyanto; Iskandar Zulkarnaen Siregar; Ani Suryani (Jurnal Penelitian Hasil Hutan, 2017)
Malapari (Pongamia pinnata (L.) Pierre) is one of the most potential biodiesel raw materials to be developed in Indonesia. The plant is natura ly distributed from Sumatera to Papua. However, oil content and its physico-chemical properties of malapari originated from Java was limitedly known. This study investigates chemical composition of malapari seeds, identifies fatty acid composition of the produced seed oil and characterises physico-chemical properties of malapari oil. Composition of chemical content of malapari seeds was analyzed through proximate analysis. Physico-chemical properties of malapari oil were analyzed using the ASTM test method. Results showed that Batukaras population is the best population to be used as biodiesel raw material source because it has the highest value of oil content. Besides, the Batukaras population has the lowest specific gravity, viscosity and acid value. Malapari oil is dominated by oleic and linoleic fatty acids which are potentia ly unsaturated fatty acids for biodiesel. Value of fatty acids (oleic and linoleic) and physico chemical properties (specific gravity and calorific value) of pongamia crude oils suggested that the five populations have been eligible for biodiesel feedstock.